MANNERS OF POLYCHLORINATED BIPHENYLS MEASUREMENT APPLIED IN EDUCATION OF TECHNICAL SUBJECTS - NEUPAUEROVA, Andrea (Trends in education, 2010)
The article introduces manners of polychlorinated biphenyls (PCBs) measurement, their toxic effects, procedure at treatment with PCBs according to valid standards in EU, that are useful in education of technical subjects.
Keywords: polychlorinated biphenyls; toxic effects; measurement; education.